Tuberculin skin test before biologic and targeted therapies: does the same rule apply for all - ATAGÜNDÜZ, MEHMET PAMİR (My University, 2022)
This study aimed to compare Tuberculin Skin Test (TST) and QuantiFERON (R)-TB Gold In-Tube (QFT-GIT) test in rheumatoid arthritis (RA) and spondyloarthritis (SpA) patients scheduled for biological and targeted synthetic disease modifying anti-rheumatic drugs (DMARDs) in a Bacillus Calmette-Guerin-vaccinated population. Adult RA (n = 206) and SpA (n = 392) patients from the TReasure database who had both TST and QFT-GIT prior to initiation of biological and targeted synthetic DMARDs were included in the study. Demographic and disease characteristics along with pre-biologic DMARD and steroid use were recorded. The distribution of TST and performance with respect to QFT-GIT were compared between RA and SpA groups. Pre-biologic conventional DMARD and steroid use was higher in the RA group. TST positivity rates were 44.2% in RA and 69.1% in SpA for a 5 mm cutoff (p < 0.001). Only 8.9% and 15% of the patients with RA and SpA, respectively, tested positive by QFT-GIT. The two tests poorly agreed in both groups at a TST cutoff of 5 mm and increasing the TST cutoff only slightly increased the agreement. Among age, sex, education and smoking status, pre-biologic steroid and conventional DMARD use, disease group, and QFT-GIT positivity, which were associated with a 5 mm or higher TST, only disease group (SpA) and QFT-GIT positivity remained significant in multiple logistic regression. TST positivity was more pronounced in SpA compared to that in RA and this was not explainable by pre-biologic DMARD and steroid use. The agreement of TST with QFT-GIT was poor in both groups. Using a 5 mm TST cutoff for both diseases could result in overestimating LTBI in SpA.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; Health Sciences; ROMATOLOJİ; Klinik Tıp; Klinik Tıp (MED); RHEUMATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Romatoloji; Rheumatology; Arthritis; Spondyloarthritis; Interferon-gamma release tests; Tuberculin test; Latent tuberculosis; GAMMA RELEASE ASSAYS; CLINICAL-PRACTICE GUIDELINES; QUANTIFERON-TB-GOLD; LATENT TUBERCULOSIS; RHEUMATOID-ARTHRITIS; CLASSIFICATION CRITERIA; ACTIVE TUBERCULOSIS; ITALIAN SOCIETY; DISEASE-CONTROL; INFECTION; Arthritis; Spondyloarthritis; Interferon-gamma release tests; Tuberculin test; Latent tuberculosis